Industrialized Construction: A Systematic Review of Its Benefits and Guidelines for the Development of New Constructive Solutions Applied in Sustainable Projects - Carlos Rojas-Herrera; Aner Martínez-Soto; Constanza Avendaño-Vera; Rodrigo Cancino Carrasco; Natalia Reyes Barbato (Applied Sciences)
In the scientific literature, it is highlighted that industrialized construction has significant comparative advantages over traditional construction, primarily in four indicators: (i) cost reduction, (ii) time reduction, (iii) increased energy performance, and (iv) reduced environmental impacts. However, there is no certainty about the range of variation of these indicators for these comparative advantages, creating uncertainty about the real impact of industrialized construction. In this work, through a systematic literature review based on PRISMA, 90 articles that met the selection criteria related to the four mentioned indicators were selected and analyzed. The results show that industrialized construction has comparative advantages over traditional construction but with a wide spectrum of variation in each of the indicators. In the cost indicator, reductions between 7% and 50% and increases between 26% and 72% are observed; in time, reductions between 9% and 50% and increases up to 32% are recorded, and reductions in energy demand between 20% and 90% are also reported. For the environmental indicators, data were only provided for projects in the design stage or for construction solutions on a scale, demonstrating the need to obtain indicators in the operational stage. It is concluded that although industrialized construction offers significant advantages, it is essential that new construction solutions consider contextual variations, initial investment, logistical challenges, and specialized labor to maximize their benefits.